Utilization of Moringa Leaves to Prevent Stunting in the Kasiyan Timur Village, Jember Regency: Pemanfaatan Daun Kelor untuk Mencegah Stunting di Desa Kasiyan Timur Kabupaten Jember - Sadam Sadewo; A. Tsani Sabhan Febrian; Eka Cemara Zevira; Khalia Hamdasi Syakirin; Kalvin Edo Wahyudi (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
Stunting is a serious health problem in developing countries, including Indonesia, which negatively affects children's growth and development. Although the prevalence of Stunting in Indonesia has decreased from 32.68% in 2010 to 27.67% in 2019, this figure is still relatively high. In Jember District, the prevalence of Stunting has been reduced from 34.9% to 29.7%, but Kasiyan Timur Village still faces significant challenges with 48 under-fives identified as stunted. The purpose of this community service activity is to provide education related to Stunting in East Kasiyan Village, Jember Regency.. In this community service activity, the community was given education about the importance of balanced nutrition, and additional food from moringa leaves.